A Sequential Approach to the Management of Posterior Glenoid Defects in RSA: Angulated BIO Versus Multiple Bioresorbable Pinning-Assisted Structural Bone-Grafting. Issue 4 (October 2021) - Imai, Shinji
Abstract : Background: Large posterior glenoid defects pose problems in reverse shoulder arthroplasty (RSA). We have adopted a sequential approach to the management of posterior glenoid defects using asymmetrical reaming, the placement of a ring graft around the central peg (bony-increased offset, or BIO), or structural bone-grafting, depending on the amount of glenoid retroversion. Furthermore, we have devised multiple bioresorbable pinning (MBP)-assisted bone-grafting, in which as many bioresorbable pins as required are inserted, from whichever aspects of the graft necessary, to achieve initial stability. Methods: We reviewed 52 shoulders with posterior glenoid defects undergoing RSA between 2014 and 2019 (mean follow-up, 4.8 years; range, 2 to 6 years). Twenty (38.5%) of the shoulders had glenoid retroversion of <15° and were treated by asymmetrical reaming (Group A), 19 (36.5%) of the shoulders had retroversion of ≥15° to <30° and were treated with asymmetrical reaming combined with angulated ring graft around the central peg (Group B), and 13 (25.0%) of the shoulders had retroversion of ≥30° and were treated with MBP-assisted bone-grafting (Group C). Results: Mean version correction was 10.6° ± 4.3° in Group A, 20.7° ± 8.8° in Group B, and 33.8° ± 9.6° in Group C. The mean postoperative active anterior elevation was 138.3° ± 12.3°, 128.3° ± 12.3°, and 126.5° ± 15.3° in the 3 groups, respectively. The mean postoperative Constant score was 66.8 ± 14.6, 62.2 ± 13.5, and 61.7 ± 16.7, respectively. The mean preoperative active anterior elevation was significantly higher in Group A than in Group C (p = 0.037). The full or partial graft-incorporation rate (≥25% of original size) was 89.5% in Group B and 100% in Group C. One glenoid fracture and 1 case of transient brachial plexus palsy occurred in Group B (10.5%), and 1 acromion fracture and 2 cases of transient brachial plexus palsy occurred in Group C (23.1%). Conclusions: The results of the present sequential approach to management of posterior glenoid defects by the 3 modalities were acceptable. The present MBP-assisted bone-grafting procedure is an effective treatment for cases of shoulder arthropathy with severe posterior glenoid defects. Angulated ring grafting around the central peg may yield equally acceptable results, although its graft-incorporation rate requires further follow-up. Level of Evidence: Therapeutic Level III . See Instructions for Authors for a complete description of levels of evidence.